Assessment of water quality and heavy metal pollution in leachate from municipal dumping ground located in Deepor Beel, a Ramsar site - Kakati, Ranjit (Acta hydrotechnica, 2024)
Municipal waste is a collection of residential, industrial, institutional, commercial, construction, and demolition waste collected by a municipality and disposed at a particular site. In poor urban areas, a large proportion of leachate is discharged, untreated directly into the closest water body. The Boragaon Garbage Dump is located inside the eastern part of Deepor Beel Wildlife Sanctuary, the only Ramsar site in Assam, Northeast India. The Boragaon Municipal Garbage dump directly releases its landfill leachate into the Deepor Beel, which increases the concentration of toxic substances in its water. In the present study, the water quality parameters and heavy metal concentration (EC, TDS, turbidity, pH, Na+, K+, Cl-, F-, BOD, DO, SO42-, PO43-, NO3-, As, Be, Cd, Ca, Cr, Cu, Fe, Mn, Mg, Ni, Pb and Zn) of the water in the outlets of Boragaon Garbage dump released into the Deepor Beel were assessed using standard methods for a one-year period. The results found were quite surprising, with very high levels of EC (8740±120 µScm-1), turbidity (693±1 NTU), BOD (458.6±1.86 mg/L), TDS (917.4±2.23 mg/L), K (53.9±0.24 mg/L), Cl- (502.28±2.96 mg/L), Al (7.21±0.06 mg/L), As (129.42±0.22 µg/L), Ni (0.102±0.002mg/L) and Pb (32.4±1 µg/L). These large amounts of physiochemical properties and heavy metals concentration in water may cause detrimental effects on the ecological communities of the Deepor Beel and the nearby human population. This Ramsar site needs an immediate solution such as the relocation of the dumping ground and better management of the existing waste to rectify the problem of deteriorating water quality, otherwise the water quality will be past the point of recovery within a decade.
Keywords: Assam; fizikalno-kemijski parametri; izcedne vode z odlagališč; landfill leachate; management; mokrišča; physio-chemical parameters; ravnanje z odpadki; toksičnost; toxicity; wetlands